Inovasi Pendidikan : Strategi Dalam Meningkatkan Mutu Pendidikan Di SMPN 2 Binjai - Yuni Syafriani; Suci Ramadhani; Amar Khairi Ahmad; Hulga Ryan Shori Sihombing (Jurnal Riset Akuntansi, 2023)
In simple terms, innovation is defined as renewal or change marked by new things. Efforts to find new things may be caused by several things to solve problems faced by a person or group. Thus, an idea or finding that is new or new changes but that have less impact on problem-solving efforts cannot be classified as innovation. Innovation as an idea, idea, practice, or object/thing that is realized and accepted as something new by a person or group for adoption. Education and learning to face various challenges and problems due to the community's increasing desire to get an education, which cumulatively demands adequate facilities and means of ensuring the quality of education provided. The development of modern science calls for a solid foundation of education and continuous mastery of abilities. It thus demands a more comprehensive education following the concept of life extended education. Developments in technology make it easier for humans to control and take advantage of nature and its environment, but which are often handled as a threat to preserving social roles. The challenges above are felt even more severe because of various problems that exist both from outside and from within the quality of education itself.